2021
DOI: 10.3390/life11030255
|View full text |Cite
|
Sign up to set email alerts
|

The Case (or Not) for Life in the Venusian Clouds

Abstract: The possible detection of the biomarker of phosphine as reported by Greaves et al. in the Venusian atmosphere stirred much excitement in the astrobiology community. While many in the community are adamant that the environmental conditions in the Venusian atmosphere are too extreme for life to exist, others point to the claimed detection of a convincing biomarker, the conjecture that early Venus was doubtlessly habitable, and any Venusian life might have adapted by natural selection to the harsh conditions in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…“Atmosphere” includes the investigation of whether gas spectral characteristics of exo-planets could be interpreted as bio-signatures, given what we know of geological traces left by the evolution of life on Earth. Life could be detected according to astronomical biosignatures such as specific proportions of atmosphere gases such as “oxygen” and reduced gases such as molecular hydrogen, methane, carbon monoxide, and phosphine [ 102 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 ].…”
Section: Discussionmentioning
confidence: 99%
“…“Atmosphere” includes the investigation of whether gas spectral characteristics of exo-planets could be interpreted as bio-signatures, given what we know of geological traces left by the evolution of life on Earth. Life could be detected according to astronomical biosignatures such as specific proportions of atmosphere gases such as “oxygen” and reduced gases such as molecular hydrogen, methane, carbon monoxide, and phosphine [ 102 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 ].…”
Section: Discussionmentioning
confidence: 99%
“…Speculation about the possibility of life in the clouds of Venus dates back to the very earliest days of our understanding of the true conditions on the planet [27] and continues to the present day (eg. [28,29]).…”
Section: Venus Todaymentioning
confidence: 99%
“…Laser experiments will be crucial for the future identification of markers of impacts, such as in the case of the Shoemaker-Levy comet impact on Jupiter (Zahnle et al, 1995), where S 2 , CS 2 , OCS, NH 3 , HCN, H 2 O, and CO have been observed (Zahnle et al, 1995). Recent studies are also associated the tentative detection of PH 3 in the atmosphere of Venus (Bains et al, 2021;Schulze-Makuch, 2021;Truong and Lunine, 2021;Bains et al, 2022) to a stochastic atmospheric corrosion of a single giant impactor or to a random elevation in the impact flux (Omran et al, 2021). A possible future milestone in astronomy is to detect very large meteors and impacts in exoplanetary atmospheres.…”
Section: Detection Of Impacts On Exoplanetsmentioning
confidence: 99%